55‐1: Invited Paper: Superiority of Monocular Augmented Reality when Continuous Viewing is Required. Issue 1 (30th May 2018) - Kitamura, Akihiko; Kinosada, Yasunori; Kimura, Takahiko; Shinohara, Kazumitsu; Sasaki, Takashi; Okumura, Haruhiko; Hotta, Aira
Abstract : We compared binocular augmented reality (AR) presentation and monocular AR presentation in a situation where continuous viewings of AR images were required. During monocular presentation, participants could detect more changes in their peripheral field of view. Thus, observers might be able to acquire more information during monocular AR presentation.